Analysis of Ecological Role and Biotechnology Potential of Marine Yeast Rhodotorula sp. in Mangrove Forest of Pari Island, Jakarta - Hutari, Andri; Anugrah, Devi; Yarza, Husnin Nahry; Faruq, Hilman; Ar Rasyid, Muhammad Luqman (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Mangrove forests have a very diverse microbial population. Among these microbes, some have the ability to convert mangrove forest organic waste into useful nutrients for the sustainability of the mangrove ecosystem. One of the species that has this ability is the marine yeast Rhodotorula sp. Apart from this ecological role, the yeast Rhodotorula sp. reported to have a lot of biotechnology potential, including as a producer of lipid omega-3, carotenoids, anti-bacterial, plant growth promoter, anti-cancer, biosurfactant, and a very potential workhorse for biotechnology applications. As a country that has the largest mangrove forest in the world, Indonesia has not reported much and has not intensified the use of marine yeast Rhodotorula sp. from Indonesian mangrove forests as a bioresource for high-value strategic products. This study aims to isolate the marine yeast Rhodotorula sp. from the mangrove forest of Pari island, Jakarta and reviewing the ecological role and biotechnological potential of these species. Marine yeast Rhodotorula sp. obtained will be cultivated and exploited its biotechnology potential in the future